"It Is More Expressive for Me": A Translingual Approach to Meaningful Literacy Instruction Through Sijo Poetry. Issue 2 (28th October 2019) - Kim, Kyung Min; Park, Gloria
Abstract : Through a qualitative analysis of one‐on‐one poetry workshops, this article explores ways in which a Korean American adult—Author 2 (Park)—develops translingual dispositions (Lu & Horner, 2013) and linguistic awareness of Korean. Situated within the translingualism literature (e.g., Canagarajah, 2017), sijo, a type of Korean poetry, became a conduit for gaining a greater insight into how meaningful literacy (Hanauer, 2012) can be enacted. The authors conceptualize the sijo composition session as a translanguaging event in that Park wrote autobiographical poems, employing multiple linguistic resources—English as an additional language and Korean as a heritage language. The analysis demonstrates that linguistic changes were frequently driven by Park's desire to communicate her message to achieve the convergence of linguistic and meaning negotiations. The findings explicate the continual process by which this translingual practice operates as recursive negotiations between language and meaning and between the two languages within the constraints of the sijo format. Those translingual negotiations became a conscious tool for self‐expression as well as a valued tool for language development. The authors argue for the incorporation of poetry writing into second language teaching to enhance learners' understanding and expressions of personal and transnational experiences. Abstract :